TRANSFORMATION OF THE DEVELOPMENT OF THE INDUSTRIAL COMPLEX IN THE DIGITAL ECONOMY - Yu. S. Polozhentseva; M. G. Klevtsova (Вестник университета)
In the modern conditions of economic development, the development of the industrial complex is being transformed with emphasis on digital technologies and high-tech production. The article considers new principles of the implementation of the state’s economic policy taking into account the challenges of the fourth industrial revolution, as well as the results of the analysis of the main indicators of industrial development, both in the world and in Russia in particular, including the assessment of the current state of innovation and technological activity of the industrial sector of the Russian economy. At the same time the authors pay special attention to the analysis of modern trends in the development of industry in countries with both a high level of high-tech production and a low level. The paper analyses the prospects of Russian industry development to justify the need for technological breakthrough strategies and technological modernization of industrial enterprises.